Pengaruh Kepemimpinan Terhadap Komitmen Anggota Kelompok Tani Maju Makmur Desa Sukaraja Kecamatan Suak Tapeh Kabupaten Banyuasin - Febri rahmadini; Rabin Ibnu Zainal; Riri Hanifa; Saudi Berlian (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2024)
This research aims to find out how leadership has a positive and significant effect on the commitment of members of advanced and prosperous farmer groups in Sukaraja village, Suak Tapeh sub-district, Banyuasin district. The sampling technique is a saturated sampling technique or census where the entire population in this study are members of the advanced and prosperous farmer group, Sukaraja village, Suak Tapeh subdistrict, Banyuasin district, totaling 91 people used as research samples. The analysis technique of this research uses Validity Test, Reliability Test, Simple Regression Analysis, t Test, and Determination Coefficient Test (R2). Based on the test of the hypothesis in this research, it shows that: 1) Based on the results of the analysis, it shows that the correlation coefficient value of the relationship between leadership and commitment is very close. 2) Leadership has a partially positive and significant effect on commitment.